Implementasi Teknologi Pembelajaran Era Digital untuk Meningkatkan Hasil Belajar Siswa di Sekolah Dasar - nastaina04; Nuraini Margareta; Febi Dwi Asviani; Glorya Pashya Koela; Herlina Herlina; Kadek Heriana (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
Rapid digital transformation has encouraged the integration of technology in education, particularly in primary schools, to improve student learning outcomes. This study aims to identify the impact of learning technology implementation on student learning outcomes, analyze the challenges in its implementation, and evaluate the positive and negative impacts that arise. Using the Systematic Literature Review (SLR) method, this article reviewed 17 relevant journals, selected based on inclusion criteria from 2019-2024. The results show that learning technology significantly improves students' engagement, motivation and understanding of learning materials. However, challenges such as limited facilities, teachers' digital competencies, as well as the technology access gap in remote areas are still major barriers. Positive impacts include increased creativity and access to learning resources, while negative impacts include the risk of dependency on technology and inequality of access. This study emphasizes the importance of continuous teacher training and improved education infrastructure to support optimal technology implementation.